Proceedings: Colorado water workshop: from the dome to the ditches: translating environmental legislation into practice - Western State College of Colorado, author; Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 1991)
The 16th Colorado water workshop was held on July 21-23, 1991 at Western State College of Colorado.
From the dome to the ditches
Presented by Western State College of Colorado.
Keywords: Water-supply -- Government policy -- Colorado -- Congresses; Water resources development -- Government policy -- Colorado -- Congresses